PENGARUH CURRENT RATION DAN DER TERHADAP ROA PADA INDUSTRI BARANG KONSUMSI TAHUN 2019 – 2022 - Cindy Aprillia Azhary,; Anditya Anggun Ratnandari,; Minto Yuwono, (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
In this era of digitalization, capital market development is increasing in Indonesia, especially the one that supports the Indonesian economy the most is the consumer goods industry. The manufacturing sector also made the largest contribution to the national Gross Domestic Product (GDP) in the second quarter of 2021, namely 17.34%. The type of research used in this research is quantitative research with a descriptive approach. In this research the independent variables used are Current Ratio (X1) and Debt to Assets Ratio (X2). Meanwhile, the dependent variable used is Return on Assets (Y). The population in this research are Consumer Goods Industrial Sector Companies on the BEI. Meanwhile, the sample is Cosmetics and Household Goods Sub- Sector Companies for 2019-2022. CR and DER simultaneously have a significant effect on the dependent variable ROA. In this test, a ttable value of 1.70113 was obtained and the α (alpha) significance level used was 0.05. Based on the table above, it is known that CR has no influence on ROA. Meanwhile, DER has an influence on ROA. The magnitude of the influence of the